KLASIFIKASI SUMBER BELAJAR DAN LANDASAN TEORI PENGGUNAAN SUMBER BELAJAR DI MI/SD - Dwi Hasanah, Kartini; Anita Silvina Wahab, Dewi; Susilowati, Samsul (CAHAYA: Journal of Research on Science Education, 2024)
Learning resources are sources of information that are presented and stored in various forms of media to assist in the learning process. These learning sources can be identified as messages, people, materials, tools, techniques and settings. Learning resources play an important role in problem solving efforts in learning in MI/SD basic education. In the learning process, teachers need to know the variety and classification of learning resources in a systematic, quality and functional manner that suits the characteristics of their students. The use of learning resources in MI/SD basic education requires a theoretical basis for learning resources so that learning becomes effective, efficient and enthusiastic. Teacher creativity in selecting and using learning resources will have a significant impact on learning. This research explores the variety, classification and theoretical basis of the use of learning resources. The aim of this research is to provide teachers with an in-depth understanding of the variety, classification and theoretical basis of MI/SD basic education. The type of research used is using library research, namely data collection, to understand and study theories from various relevant literature.